Low Incidence of Prosthesis-Patient Mismatch Following Extremely Small Transcatheter Aortic Valve Replacement with 20-mm Sapien 3 - Okajima, Kazue; Komatsu, Ikki; Seto, Todd B. (International Journal of Angiology, 2021)
Transcatheter aortic valve replacement has been developed as an emerging technique to treat patients with aortic valve disease. However, safety and outcome data on extremely small transcatheter heart valves (THV) is limited. We aimed to assess hemodynamic profiles and clinical outcome of very small balloon expandable THVs with 20-mm Sapien 3 (SP3).We examined data for all patients who received third-generation SP3 THV at a single hospital. Complications and clinical outcomes were defined based on the VARC-2 criteria. Postoperative prosthesis-patient mismatch (PPM) was defined as indexed effective orifice area (EOA) < 0.85 cm2/m2. We compared clinical characteristics and outcome between patients with 20-mm (n = 21), 23-mm (n = 67), and 26- or 29-mm (n = 113) sized valves.The 20-mm group included significantly higher number of Asian and female populations with lower body surface area. The baseline CT annular area in the 20-mm group was 316.5 ± 24.9 mm2. There was no significant difference between groups in procedural mortality or early safety at 30 days. The higher procedural complication was observed in 20-mm group due to significant differences in minor vascular and bleeding complications. Despite higher post-THV gradients and smaller indexed EOA in 20-mm group, no PPM was observed in 20-mm group. The mortality at 30 days and 1 year in 20-mm group was 4.8% and 16.7%, respectively.The patients who received very small THVs with 20-mm SP3 did not result in PPM and experienced favorable early safety and midterm outcome in our cohort.
Keywords: transcatheter aortic valve replacement; prosthesis-patient mismatch; small aortic annulus; aortic stenosis; outcome